Counseling Program Based on Android as Digital Consultation Media - Haling, Abdul; Kasim, Muhammad; Nurhikmah, Nurhikmah H; Anas, Muhammad; Ramli, Abdul Malik (LPPM Undiksha, 2023)
Online tutoring can be provided ethically and have effective results. However, the context surrounding the application of online counselling is debatable, with limited research having been conducted examining the use of online counselling. This study aims to develop an Android-based e-counselling guidance program. This type of research is created using the Alessi and Trollip development model, which consists of 3 stages: planning, design, and development. The research subjects were 29 students and 1 teacher/counsellor. This study's data collection methods use questionnaires, tests and interview guidelines. The data collection instrument uses a questionnaire sheet. Data analysis techniques using qualitative and quantitative descriptive analysis. The research results are that the developed media is validated by media experts and material experts, with the validation results obtained an average score of 3.4 (very valid) and an average score of 3.7 (very valid) by media experts. E-Counselling guidance through field tests meets very practical criteria. The e-counselling guidance program facilitates the consultation process for students and teachers/counsellors, improving student learning outcomes. The study implies that e-counselling can be included in guidance and counselling services by school counsellors.